Early Schizophrenia Diagnosis with 3D Convolutional Neural Network - Ashraf, S.M. Nabil; Oikko, Isbat Mashiat; Saha, Chayan; Anik, Md. Rakib Enam (Brac University, 2021)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2021.